Heat transfer in packed beds: experimental evaluation of one-phase water flow - Thoméo, J. C. [UNESP] (2004)
Experimental heat transfer studies were carried out in 50.8 mm diameter packed beds of glass beads percolated by water and heated from the wall. The tube-to-particle diameter ratio (D/d p) ranged from 1.72 to 13.7 and the water flow rate from 1.1 to 9.9 l/min. Bed heights ranged from 100 mm to 700 mm. The radial temperature was measured above the bed surface by five aligned sheathed thermocouples. Variations in angular temperature were observed, independent of both radial position and particle diameter. Results of repeated tests with the same packing and with repacking did not differ statistically. The radial temperature profile at the bed entrance, measured by a ring-shaped sensor, was uniform except very close to the tube wall.